Analisis Komposisi Sampah Sebagai Dasar Pemilihan Metode Pengelolaan Sampah pada Green Building - Ananda Cinta Laura; Restu Hikmah Ayu Murti (Universitas Maritim AMNI Semarang, 2024)
The waste piles in the landfill pose a higher environmental hazard compared to the waste at its source due to the potential formation of leachate and air emissions. Consequently, waste management from the source is essential to minimize the amount of waste in the landfill. The waste management methods at each location typically vary based on the composition, characteristics, and quantity of waste present in that specific area. In this study, an analysis of waste piles at facility X was conducted through the process of sorting and weighing the waste during October 2023, with the objective of providing research findings that can be utilized to determine suitable waste management options for the location. The research revealed that the dominating composition of the waste consists of organic waste, with garden waste accounting for 55.95% and food residue comprising 10.75%. Composting was selected as the recommended alternative for waste treatment in the area. Garden waste, primarily composed of dry leaves, is suggested to be treated using the pile composting method, while food residue is suggested to be treated through a combination of Black Soldier Fly larvae biotechnology and Takakura composting.